Changes in Neuronal Excitability by Activated Microglia: Differential Na+ Current Upregulation in Pyramid-Shaped and Bipolar Neurons by TNF-α and IL-18 - Klapal, Lars; Igelhorst, Birte A.; Dietzel-Meyer, Irmgard D. (Frontiers in Neurology, 2016)
Microglia are activated during pathological events in the brain and are capable of releasing various types of inflammatory cytokines. Here we demonstrate that the addition of 5% microglia activated by 1 µg/ml lipopolysaccharides (LPS) to hippocampal cultures up-regulates Na+ current densities (INavD) of bipolar as well as pyramid-shaped neurons, thereby increasing their excitability. Deactivation of microglia by the addition of 10 ng/ml transforming growth factor-β (TGF-β) decreases INavD below control levels suggesting that the residual activated microglial cells influence neuronal excitability in control cultures. Preincubation of hippocampal cultures with 10 ng/ml tumor necrosis factor-α (TNF-α), a major cytokine released by activated microglia, up-regulated INavD significantly by ~30% in bipolar cells, whereas in pyramid-shaped cells the up-regulation only reached an increase of ~14%. Incubation of the cultures with antibodies against either TNF-receptor 1 or 2 blocked the up-regulation of INavD in bipolar cells, whereas in pyramid-shaped cells increases in INavD were exclusively blocked by antibodies against TNF-receptor 2, suggesting that both cell types respond differently to TNF-α exposure. Since additional cytokines, such as interleukin-18 (IL-18), are released from activated microglia we tested potential effects of IL-18 on INavD in both cell types. Exposure to 5-10 ng/ml IL-18 for 4 days increased INavD in both pyramid-shaped as well as bipolar neurons, albeit the dose-response curves were shifted to lower concentrations in bipolar cells. Our results suggest that by secretion of cytokines microglial cells up-regulate Na+ current densities in bipolar and pyramid-shaped neurons to some extent differentially. Depending on the exact cytokine composition and concentration released this could change the balance between the activity of inhibitory bipolar and excitatory pyramid-shaped cells. Since bipolar cells show a larger up-regulation of INavD in response to TNF-α as well as respond to smaller concentrations of IL-18, our results offer an explanation for the finding, that in certain conditions of brain inflammations periods of dizziness are followed by epileptic seizures.